Loss of JAM-C leads to impaired esophageal innervations and megaesophagus in mice. Issue 7 (1st October 2016) - Ye, M.; Zhang, Q.; Xu, X.; Zhang, Q.; Ge, Y.; Geng, P.; Yan, J.; Luo, L.; Sun, Y.; Liang, X.
Summary: Megaesophagus is a disease where peristalsis fails to occur properly and esophagus is enlarged. The etiology and mechanism of megaesophagus are not well understood. In this study, we reported that junctional adhesion molecule C (JAM-C) knockout mice on a C57/B6 background developed progressive megaesophagus from embryonic day (E) 15.5 onward with complete penetrance. JAM-C knockout mice exhibited a significant reduction in the number of nerve fibers/ganglia in the wall of the esophagus. However, histological analysis revealed that the esophageal wall thickness and structure of JAM-C knockout mice at embryonic stages and young adult were comparable to that of control littermates. Thus, megaesophagus observed in JAM-C knockout mice could be attributed, at least in part, to impaired esophageal innervations. Our data suggest JAM-C as a potential candidate gene for human megaesophagus, and JAM-C knockout mice might serve as a model for the study of human megaesophagus.